(untitled) (African Journal of Law and Politics, 2023)
The Protection of refugees has always been a fundamental issue under international law. The 1951 Convention being the focal instrument in guaranteeing the protection of the rights of refugees particularly when dealing with that of freedom of movement obliges states to take necessary measures in ensuring that refugees who lawfully enter their territory should be adequately protected. In conversant with the aforementioned Convention, Cameroon in complying with the 1951 Convention has enacted the 2005 law in its view of protecting this fundamental right of a refugee. Even though with the existence of the relevant local legislation as to the protection of a refugee, ensuring this right as to freedom of movement has been challenging, as refugees tirelessly continue to face violations of this right throughout their stay in the Cameroonian territory. Problems such as xenophobia, racism, discrimination, and a host of others experienced by these refugees becomes detrimental to them when dealing with their freedom of movement. The objective of this paper is to examine whether the State of Cameroon in traverse of its local legislation as to refugee protection has been able to respect international prescriptions when dealing with protecting refugees’ right to freedom of movement. From the above objective and problematic, one can say that even though huge efforts have been put in place by the State of Cameroon when dealing with the refugee’s right to freedom of movement, these efforts and initiatives are insufficient and ineffective as refugees continue to experience violation on this inviolable right. It is therefore in this nimble that revisiting the provision of the various local legislation is important and putting in place strict compliance measure for the effective protection of this right of refugee is of utmost standing.